2020
DOI: 10.1002/pip.3356
|View full text |Cite
|
Sign up to set email alerts
|

Surface preparation for 10% efficient CZTSe solar cells

Abstract: Kesterite‐based solar cells suffer from a large open‐circuit voltage deficit, which largely arises from carrier recombination at the buffer interface. In this study, we compare two strategies to passivate the absorber surface in order to fabricate devices with power conversion efficiency higher than 10% and an open‐circuit voltage deficit as low as 306 mV. These two strategies consist of annealing in air or performing a chemical etching of the absorbers before buffer deposition. They lead similarly to a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Moreover, the XPS profile in Figure e shows the presence of Ag in the ACZTSe samples, with Ag 3d 3/2 and Ag 3d 5/2 peaks at ∼368.1 and 372.1 eV (δ E ≈ 4.0 eV), respectively. This reveals that silver was present in Ag + form, in agreement with other reports. …”
Section: Resultssupporting
confidence: 93%
“…Moreover, the XPS profile in Figure e shows the presence of Ag in the ACZTSe samples, with Ag 3d 3/2 and Ag 3d 5/2 peaks at ∼368.1 and 372.1 eV (δ E ≈ 4.0 eV), respectively. This reveals that silver was present in Ag + form, in agreement with other reports. …”
Section: Resultssupporting
confidence: 93%
“…According to Grenet et al., the peaks of Zn 2p3/2 and Sn 3d5/2 moving toward lower binding energy after AS treatment is considered to be due to the oxidation/deoxidation of the ZnSe and SnSe x phases on the surface, respectively. [ 16 ] Therefore, under the same AS treatment time, more Zn and Sn are etched, resulting in an increase of the Cu/(Zn+Sn) ratio for sample Kes‐Al 2 O 3 ‐AS. Overall, the surface composition of the absorber is within a reasonable range, and the Cu/(Zn+Sn) value for sample Kes‐Al 2 O 3 ‐AS is more ideal as a Cu‐poor surface, which is suitable for the preparation of efficient solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that ammonium sulfide ((NH 4 ) 2 S, referred to as AS) solution treatment on the absorber layer can improve the film's surface properties. [16][17][18][19][20][21][22][23] For example, Buffière et al selectively removed the secondary phase on the surface and modified the surface chemical state by dipping CIGS absorber into AS solution, and the minority carrier lifetime increased about 6-11 ns with different treatment times. [17] The same treatment has been employed for CZTSSe, too.…”
Section: Introductionmentioning
confidence: 99%
“…Post-heat treatment in air induces oxygen from the ambient atmosphere to form a native oxide layer on the surface 257 and diffuse into CZTSSe absorbers along grain boundaries (GBs), 258 which has been reported to contribute to improving device performance. 91,95,168,259 This approach can cause local composition uctuation of the absorbers, such as Cu and Se decient and Sn-enriched composition at the GBs (Fig. 10a), 168 and Zn enrichment on the surface.…”
Section: S-se Anion Engineeringmentioning
confidence: 99%